Analisis Transaksi Terapeutik Sebagai Sarana Perlindungan Hukum Bagi Pasien - Anggraeni Endah Kusumaningrum (Universitas Merdeka Madiun, 2019)
This paper aims to know and analyze therapeutic transactions as a means of legal protection for patients. Therapeutic transactions are agreements between physicians and patients who authorize the physician to perform activities to provide health services to patients based on the skills and skills possessed by the doctor. The legal relationship in such therapeutic transactions creates rights and obligations that must be obeyed and implemented by each party. This research uses normative juridical approach method with primary data source is secondary data supported by primary data. Primary data is obtained directly through interviews and secondary data in the form of legal materials, both primary, secondary and tertiary which will be analyzed qualitatively through data collecting, data reduction, data presentation and verification of data or conclusions. The results obtained that therapeutic transactions position physicians and patients, on the same relationship with the hope of providing legal protection for the parties, but in fact the norms have not been able to provide legal protection. That happens because there is no arrangement of the implementation of the transaction therapeutic consistently.